MANAGING TEST ANXIETY: RESEARCH ON SRI LANKAN UNIVERSITY STUDENTS - Jayasuriya , Nalini (International Research Journal of Sociology, Psychology and Anthropology, 2024)
The Sri Lankan education system is structured into three key stages, spanning 13 years, starting from primary school to college-level education. The journey comprises primary education (Grades 1-5), junior secondary education (Grades 6-9), senior secondary education (Grades 10-11), and college-level education (Grades 12-13). Notably, the Grade 5 scholarship and General Certificate Examination, Ordinary Level (GCE O/L), are highly competitive, as they hold the key to better educational opportunities. Success in the Grade 5 scholarship exam opens doors to improved schools, while a strong performance in the O/L exam offers students the chance to choose between different subject streams, including Arts, Science, Maths, and Commerce. Furthermore, the GCE Advanced Level (GCE A/L) examination is a pivotal point in the educational journey, as it grants access to government universities. Exceptional achievers at the A/L examination can secure admission to the national university system.